Plant aquaporins: Roles in plant physiology - Li, Guowei; Santoni, Véronique; Maurel, Christophe (Biochimica et biophysica acta, 2014)
Aquaporins are membrane channels that facilitate the transport of water and small neutral molecules across biological membranes of most living organisms. Here, we present comprehensive insights made on plant aquaporins in recent years, pointing to their molecular and physiological specificities with respect to animal or microbial counterparts. In plants, aquaporins occur as multiple isoforms reflecting a high diversity of cellular localizations and various physiological substrates in addition to water. Of particular relevance for plants is the transport by aquaporins of dissolved gases such as carbon dioxide or metalloids such as boric or silicic acid. The mechanisms that determine the gating and subcellular localization of plant aquaporins are extensively studied. They allow aquaporin regulation in response to multiple environmental and hormonal stimuli. Thus, aquaporins play key roles in hydraulic regulation and nutrient transport in roots and leaves. They contribute to several plant growth and developmental processes such as seed germination or emergence of lateral roots. Plants with genetically altered aquaporin functions are now tested for their ability to improve plant resistance to stresses. This article is part of a Special Issue entitled Aquaporins. •The multiplicity of aquaporins in plants reflects a high diversity of cellular localizations and substrates.•Aquaporins play key roles in hydraulic regulation and nutrient transport in roots and leaves.•Aquaporins mediate regulation of water transport in response to multiple environmental and hormonal stimuli.